EFFECT OF PHOTOPERIOD SENSITIVITY ON YIELD AND OTHER ECONOMIC TRAITS OF NEW STRAINS OF BASMATI RICE (ORYZA SATIVA L.) - M. Akhter; M. Ahmad; M. Ramzan (Journal of Animal and Plant Sciences, 2007)
Photoperiod sensitivity is one of the most important character which acts as an indicator to distinguish a basmati variety from non-basmati variety. Twelve rice promising lines i.e., 98801, 98410, 98316, 99417, 97502, 99512, 98410, 99513, 98506, 98408, 5261-1-2 along with Super Basmati as check variety were transplanted on six different dates (16May to 1st August) with an interval of fifteen days to test the basmati behavior of new strains. Super Basmati in all the six dates flowered in the last week of September and first week of October irrespective of its time of transplanting. Super Basmati showed a remarked increase in plant height in first (138 cm) and 2nd date (127cm) due to prolonged vegetative period while it showed a considerable decrease in plant height in last date (101cm) due to reduced vegetative phase. New strains 98316, 99417and 98408 reflected the same behavior and appeared to be true basmati strains. Whereas rest of the strains performed equally good in all the dates and remained unaffected by the different transplanting dates and appeared to be non-basmati strains. Most of the promising lines gave good yield when transplanted from 1st July to 16th July. 99512 and 99513 behaved differently, paddy yield of these genotypes reduced when transplanted late. In conclusion, photoperiod sensitivity is an important character of basmati rice. Super basmati is an improved form of Basmati rice and photosensitivity is its major character. Besides this variety, 98316, 99417 and 98408 are also true basmati strains.
Keywords: Photoperiod sensitivity; Basmati rice varieties; Transplanting dates.